Distribuição de elementos potencialmente tóxicos no rio Sorocaba subsequente a sua recuperação - Silva, Caroline Ferreira da (2023)
The ability of natural environments to provide ecosystem goods and services is affected to varying degrees by the intensification of human activities. The degradation of urban river ecosystems poses a serious threat to the maintenance of terrestrial life and to sustainable urban development worldwide. Consequently, great efforts have been devoted to the environmental restoration of urban rivers worldwide. The objective of this study was to evaluate the effectiveness of aquatic environmental remediation programs carried out worldwide, and to analyze the distribution of potentially toxic elements (PTEs) in an urban river that underwent a water remediation program, the Sorocaba River). Among the results of the first investigation, it is clear throughout the discussion that there has been a notorious evolution in the implementation of urban river recovery programs worldwide in the period from 2010 to 2022, and that these ecosystems were mostly affected by domestic and industrial effluent discharge, as well as having their surroundings subjected to high and rapid urbanization and suppression of riparian vegetation. This scenario is similar to that found in the Sorocaba River, based on literature data. In this context, the second investigation identified a possible compromising of the quality levels of the Sorocaba River, with regard to the concentration of TPEs, seven years after the end of the depollution program implemented. Therefore, the water body requires action to remediate the environmental problems in force. Concentrations were found above the maximum allowed by Brazilian legislation regarding the analysis of physical-chemical and hydrobiological parameters essential to water quality, in addition to negative impacts on the Sorocaba River biota and other aquatic compartments associated to the ecosystem, such as the Itupararanga reservoir. These alterations were probably caused or intensified by anthropic activities. In view of the above, it is possible to understand the relevance of investigations regarding the re-establishment of the ecological quality of urban aquatic ecosystems and the environmental panorama of the Sorocaba River.